Existing Situation of Digital Pedagogy in the Mathematics Classroom - Acharya, Umesh (Ganeshman Darpan, 2023)
This article examines the existing situation of digital pedagogy in mathematics classrooms at Tribhuvan University, focusing on the skills and activities of mathematics teachers. Digital pedagogy, the integration of ICT tools and techniques in teaching, can potentially enhance teaching and learning activities. However, there are challenges in implementing digital pedagogy, such as limited access to technology and inadequate teacher preparation programs. This study utilized a cross-sectional research design with quantitative methodology. Data were collected from mathematics teachers of constituent campuses at Tribhuvan University using self-constructed closed-structure questionnaires. The results indicated that mathematics teachers possess varying levels of digital skills, with proficiency in producing documents and using emails but lower proficiency in developing questions and mathematical documents using Latex. The teachers frequently use the Internet to collect information and employ digital presentation tools. However, the usage of online resources and platforms for learning materials and homework posting was occasional. The findings underscore the importance of targeted training and resource provision to enhance digital skills among mathematics teachers. Tribhuvan University should prioritize technology access, improve teacher preparation programs, and promote digital literacy. By addressing these challenges, Tribhuvan University can effectively integrate digital pedagogy in mathematics classrooms, leading to enhanced teaching and learning experiences and improved student outcomes.